Transanal approach after preoperative imatinib treatment of a rectal gastrointestinal stromal tumors with external anal sphincter invasion: A case report. (August 2021) - Hisanaga, Makoto; Nosanaka, Takashi; Maruta, Hiroshi; Maruyama, Keizaburou; Fukuoka, Hidetoshi; Yamaguchi, Hiroyuki
Abstract: Introduction and importance: Rectal gastrointestinal stromal tumors (GISTs) are rare, and preserving anorectal function can be challenging. We report the case of a patient with rectal GIST with external anal sphincter invasion, treated via the laparoscopic and transanal approaches. Case presentation: A 61-year-old man with locally advanced GIST in the right anterolateral wall of the lower rectum was examined. Lower endoscopy revealed a 50-mm submucosal tumor located 4 cm from the anal verge. On immunohistochemistry, the biopsy specimen tested positive for CD34 and C-KIT, and the patient was diagnosed with GIST. Abdominal magnetic resonance imaging (MRI) revealed external anal sphincter infiltration. Because of the large tumor size and proximity to the anal verge, preserving the anus was challenging, and colorectal resection was avoided. Instead, neoadjuvant therapy with imatinib was administered to facilitate local resection of the tumor. Post-treatment MRI showed a reduction in tumor size (30 × 20 × 30 mm), and surgery was performed. We identified an appropriate resection line for diplomatic sphincter resection of the infiltrated area by laparoscopy alone. Thus, we performed a hybrid surgery using the laparoscopic and transanal approaches. The patient had an unremarkable postoperative course and was discharged on postoperative day 23. Clinical discussion: No study has reported cases of rectal GIST with external anal sphincter invasion wherein anal function was preserved. Here, imatinib was administered preoperatively, and hybrid surgery was performed using the transanal and laparoscopic approaches. Conclusion: Preoperative treatment and surgery preserved anorectal function in a patient with a massive rectal GIST. Highlights: The principle of treatment for GISTs is complete resection. There are no reports on rectal GIST preserved anal function. Recently, neoadjuvant treatment with imatinib has been used. Laparoscopic and transanal approaches are able to identify the resection line.